2017
DOI: 10.1038/s41598-017-05117-2
|View full text |Cite
|
Sign up to set email alerts
|

Potassium as a pluripotency-associated element identified through inorganic element profiling in human pluripotent stem cells

Abstract: Despite their well-known function in maintaining normal cell physiology, how inorganic elements are relevant to cellular pluripotency and differentiation in human pluripotent stem cells (hPSCs) has yet to be systematically explored. Using total reflection X-ray fluorescence (TXRF) spectrometry and inductively coupled plasma mass spectrometry (ICP-MS), we analyzed the inorganic components of human cells with isogenic backgrounds in distinct states of cellular pluripotency. The elemental profiles revealed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Additionally, our work adds to the molecular mechanisms that have associated membrane potential with stem cells differentation 12,14,[60][61][62] . Of note, previous work has suggested that K + itself may have signaling properties that affect the directed differentiation of hESCs 63 . However, our study indicates that it is V m and not K + itself that is critical.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, our work adds to the molecular mechanisms that have associated membrane potential with stem cells differentation 12,14,[60][61][62] . Of note, previous work has suggested that K + itself may have signaling properties that affect the directed differentiation of hESCs 63 . However, our study indicates that it is V m and not K + itself that is critical.…”
Section: Discussionmentioning
confidence: 98%
“…Our study was focused on relations between K + transport and stem cell proliferation. Recently, using reflection X-ray fluorescence spectrometry and mass spectrometry, the extensive research of the inorganic components in human stem cells in distinct states of cellular pluripotency was performed 51 . This study revealed that intracellular K + content differs considerably between non-pluripotent and pluripotent cells (hPSCs), and the perturbations of K + homeostasis in the presence of pharmacological drugs affect the intracellular signaling in hPSCs and the cell reprogramming for induced hPSCs production.…”
Section: Discussionmentioning
confidence: 99%
“…This means, that despite the lack of significant concentration differences, K + may be important for initiating cell proliferation as the intracellular ion that participates in regulation of volume and water content. Indeed, iincreasing evidence indicate that K + channels of plasma membrane are involved in regulation of cell proliferation: their expression and function can be regulated by the cell cycle, and inhibition of K + channel activity results in cell cycle arrest 12,26,27,56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…We also found age-dependent decrease in K i per g of cell protein in growing cultures of human mesenchymal stem cells 26 . Of interest, cell K + content assayed by X-ray fluorescence spectrometry and mass spectrometry differs considerably between human pluripotent cells and non-pluripotent cells 27 .…”
Section: Introductionmentioning
confidence: 99%